Discrete element simulation of wire-mesh retaining systems: An insight into the mechanical behaviour. (June 2021) - Pol, Antonio; Gabrieli, Fabio
Abstract: This work presents a new study approach for the evaluation of the behaviour of anchored mesh systems with the Discrete Element Method (DEM) in slope stability applications. Firstly, the mesh model is validated against experimental punch test results. Secondly, it is applied to an idealized field condition in which a secured drapery system is loaded by an unstable debris volume. The non-linear force-displacement response of the mesh is characterized by small deformations to the failure conditions. Furthermore, the force transmitted to the anchors and the stress distribution in the steel wires surrounding the anchors are discussed. A local wedge-shaped failure mechanism, associated with each single mesh panel, is identified as typical of the failure process occurring in the debris layer. Finally, the influence of the thickness of the debris layer and of the anchors' pattern on the mesh mechanical response is investigated.